EKSEKUSI PUTUSAN HAKIM DALAM SENGKETA PERDATA DI PENGADILAN NEGERI SEMARANG - Tony Rachardiyanto (Universitas Stikubank, 2023)
This article is based on research that aims to describe the implementation of civil case decisions at the Semarang District Court and its constraints. This type of research is descriptive qualitative. It was found that the implementation of civil case decisions in the Semarang City court began with the indictment or submission of execution by the appellant and ended with the execution of confiscation. The obstacles are (1) the high cost as a guide for the Petitioners; (2) the lack of qualified personnel; and (3) competition or rejection of the accused. Efforts to overcome these obstacles are: (1) the head of the district court encourages both parties to compromise between the initiator of the indictment and his opponent (the accused) amicably; (2) sending confiscation replacement personnel to summon the conflicting parties and proposed additional personnel but was not successful; and (3) confiscation officials inform or send unresolved issues via electronic devices to the City of Semarang to postpone implementation.